Processing of Paired Click-Tone Stimulation in the Mice Inferior Colliculus - Wang, Ningqian; Lin, Minlin; Qiao, An; Xiao, Zhongju (Frontiers in Physiology, 2019)
The inferior colliculus (IC) is known as a neuronal structure involved in the integration of acoustic information in the ascending auditory pathway. However, the processing of paired acoustic stimuli containing different sound types, especially when they are applied closely, in the IC remains poorly studied. We here firstly investigated the IC neuronal response to the paired stimuli comprising click and pure tone with different inter-stimulus (click-tone) intervals using in vivo loose-patch recordings in anesthetized BALB/c mice. It was found that the total acoustic evoked spike counts decreased under certain click-tone interval conditions on some neurons with or without click-induced supra-threshold responses. Application of click could enhance the minimum threshold of the neurons responding to the tone in a pair without changing other characteristics of the neuronal tone receptive fields. We further studied the paired acoustic stimuli evoked excitatory/inhibitory inputs, IC neurons received, by holding the membrane potential at -70/0 mV using in vivo whole-cell voltage-clamp techniques. The curvature and peak amplitude of the excitatory/inhibitory post-synaptic current (EPSC/IPSC) could be almost unchanged under different inter-stimulus interval conditions. Instead of showing the summation of synaptic inputs, most recorded neurons only had the EPSC/IPSC with the amplitude similar as the bigger one evoked by click or tone in a pair when the inter-stimulus interval was small. We speculated that the IC could inherit the paired click-tone information which had been integrated before reaching it.